Evaluation of Cardiac function in COPD patients and correlation with disease severity: A cross sectional study - Basak, Subhadip; Mukherjee, Rishav; Chowdhury, Sampurna; Roy, Sabyasachi; Banerjee, Reet; Bhattacharya, Raja (Asian Journal of Medical Sciences, 2021)
Background: Chronic obstructive pulmonary disease (COPD) has considerable effects on cardiac functions, including those of the right ventricle, left ventricle, and pulmonary blood vessels. Most of the increased mortality associated with COPD is due to cardiac involvement. Echocardiography provides a rapid, non-invasive portable, and almost accurate method to evaluate the right ventricle function, right ventricular filling pressure, tricuspid regurgitation, left ventricular function, and valvular functions. Early diagnosis and intervention for cardiac comorbidities would reduce mortalities in COPD. Aims and Objectives: This study was undertaken to evaluate cardiac function with echocardiography in COPD patients which may further help to assess the prognosis and assist in identifying the individuals likely to suffer increase morbidity and mortality. Materials and Methods: A hospital based cross sectional study in which 100 patients over a period of 1 year were selected according to inclusion and exclusion criteria and cardiac comorbidities were observed in COPD patients by 2D echocardiography. All patients were studied on the basis of following variables- Demographic evaluation, Clinical evaluation, Pulmonary function test, echocardiography. Results: Distribution of the study population showed that a large number of COPD patients developed cardiac complication - Right and left ventricular dysfunction and pulmonary arterial hypertension especially in higher grades of COPD patients which can contribute to increased morbidity and mortality. Conclusion: Cardiac dysfunction is quite common in COPD patients, especially in the higher grades of COPD. So, we recommend that echocardiography should be included in routine evaluations of all COPD patients for early diagnosis and management of cardiac complications.